Clozapine's critical role in treatment resistant schizophrenia: ensuring both safety and use. Issue 9 (1st September 2016) - Remington, G.; Lee, J.; Agid, O.; Takeuchi, H.; Foussias, G.; Hahn, M.; Fervaha, G.; Burton, L.; Powell, V.
ABSTRACT: Introduction : Clozapine was first introduced as an antipsychotic in the 1970's but a cluster of deaths, later linked to the drug's risk of agranulocytosis, led to its withdrawal in most countries. However, work in the 1980's established its unique efficacy in treatment resistant schizophrenia (TRS), which constitutes as many as 30% of those with the illness. Clozapine was reintroduced with this indication shortly thereafter, but because of this risk its use requires routine hematologic monitoring. Areas covered : An update is provided regarding clozapine's risk of neutropenia, agranulocytosis, and associated mortality. In addition, updates are provided on other side effects, specifically myocarditis and bowel obstruction, as evidence suggests these are more common than agranulocytosis and associated with higher mortality rates. Expert opinion : Clozapine remains the only treatment indicated in TRS, but it is dramatically underutilized. Clearly there are serious side effects associated with its use, and while the focus has historically been on hematologic concerns, we highlight other side effects that also demand systematic monitoring. Because it is the only effective treatment option we have for TRS, though, efforts must be implemented that ensure its use in this population while maximizing safety.